2021
DOI: 10.3390/v14010045
|View full text |Cite
|
Sign up to set email alerts
|

Severity Biomarkers in Puumala Hantavirus Infection

Abstract: Annually, over 10,000 cases of hemorrhagic fever with renal syndrome (HFRS) are diagnosed in Europe. Puumala hantavirus (PUUV) causes most of the European HFRS cases. PUUV causes usually a relatively mild disease, which is rarely fatal. However, the severity of the infection varies greatly, and factors affecting the severity are mostly unrevealed. Host genes are known to have an effect. The typical clinical features in PUUV infection include acute kidney injury, thrombocytopenia, and increased vascular permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…A recent review summarized severity biomarkers in PUUV orthohantavirus infection ( 12 ). However, almost all mentioned biomarkers are difficult to measure, need special laboratory platforms, or are cost-intensive.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review summarized severity biomarkers in PUUV orthohantavirus infection ( 12 ). However, almost all mentioned biomarkers are difficult to measure, need special laboratory platforms, or are cost-intensive.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, future studies are required to confirm that these identified markers correlate specifically with PUUV-induced thrombocytopenia and AKI, which could play a role in the triage of patients for in- or outpatient treatment. Additionally, it would be of great interest to include other recently discovered blood markers that show the potential of being associated with severe disease, such as complement activation and glycoprotein YKL-40 [ 28 , 29 , 30 ]. Altogether, these findings demonstrate that specific biomarkers of interest in light of PUUV pathogenesis significantly differ between PUUV patients with different disease severity in terms of platelet counts and kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…We have detected and evaluated numerous biomarkers in PUUV HFRS (NE), as recently reviewed [ 62 ]. This has been performed with two aims: (i) to understand better the pathogenesis of NE [ 4 ] and (ii) to use the biomarkers to predict the disease severity and long-term consequences of the disease [ 63 , 64 , 65 , 66 ].…”
Section: Role Of Different Factors In the Variationmentioning
confidence: 99%
“…The list of biomarkers evaluated is long: interleukin-6, C-reactive protein (CRP), pentraxin-3, indoleamine 2-3-dioxygenase, cell-free DNA, soluble urokinase-type plasminogen activator, resistin, YKL-40, galectin-3 binding protein (Gal-3BP; Mac-2 binding protein), GATA-3, neutrophil gelatinase-associated lipocalin (NGAL), and procalcitonin [ 62 ].…”
Section: Role Of Different Factors In the Variationmentioning
confidence: 99%